Digital Transformation of Balista Sushi through BPMN and SWOT Analysis - Ardifadika Lorenza; Nur Nur (Penerbit Goodwood, 2026)
Purpose: The culinary business continues to grow rapidly in Bandung, with increasing competition and high customer expectations. This research aims to analyze the business development strategy of Balista Sushi & Tea throught Business Process Model and Notation (BPMN) and SWOT analysis. The focus is on operational efficiency and marketing strategy in order to support digital transformation efforts in small and medium enterprises (SMEs). Methodology/approach: This study employs a descriptive qualitative approach through interviews, observations, and questionnaires with six managerial team members at Balista, and uses BPMN to model business processes while proposing Accurate ERP as a digital solution for inventory management issues. Results/findings: The research indicates that Balista is positioned in Quadrant I of the SWOT matrix, reflecting strong internal strengths and favorable growth opportunities. However, its inventory, purchasing, and sales processes remain manual and fragmented, and the implementation of Accurate ERP is expected to enhance integration, efficiency, and data-driven decision-making. Conclusions: This research concludes that the integration of BPMN, SWOT, and ERP in the digital transformation process can significantly improve operational efficiency and marketing competitiveness for SMEs in the culinary sector. Limitations: The study is limited to one Balista branch (Kota Baru Parahyangan) and a limited number of internal respondents, which may not reflect the overall operational conditions across all branch. Contributions: This study contributes to digital transformation literature in culinary SMEs by proposing an integrated framework that combines BPMN, SWOT, GAP analysis, and Accurate ERP to improve operational efficiency and marketing competitiveness in Indonesian SMEs.